The Discourse of Friday Sermon in Indonesia: A Socio-Cultural Aspects and Language Function Studies - Saddhono, Kundharu; Rakhmawati, Ani (Jurnal Komunikasi Islam, 2018)
This research attempted to explain the Friday sermon by analyzing the structure of its discourse, the selection and composing of its topics, the functions of its codes and code-switching, the function of its speech acts, and the characteristics of its language and specific terms. By using descriptive and qualitative, this study found that the Friday sermon contained oral discourse which has a regular and specific structure. The strategies of the composition of the topics consisted of quotation, storytelling, usage of popular expressions. Whilst the forms of the codes and code-switching involve Arabic, Indonesian, local languages [Javanese], and English languages. In addition, the utterances of the sermon contain all forms of speech acts and various terms appeared in the sermons indicating that the Friday sermon functions as a register or usage of language in a particular field.